Elevated methane alters dissolved organic matter composition in the Arctic Ocean cold seeps - Sert, Muhammed Fatih; Schweitzer, Hannah D.; de Groot, Tim R.; Kekäläinen, Timo; Jänis, Janne; Bernstein, Hans C.; Ferré, Bénédicte; Gründger, Friederike; Kalenitchenko, Dimitri; Niemann, Helge (Frontiers in Earth Science, 2023)
Cold seeps release methane (CH4) from the seafloor to the water column, which fuels microbially mediated aerobic methane oxidation (MOx). Methane oxidising bacteria (MOB) utilise excess methane, and the MOB biomass serves as a carbon source in the food web. Yet, it remains unclear if and how MOx modifies the composition of dissolved organic matter (DOM) in cold seeps. We investigated MOx rates, DOM compositions and the microbial community during ex-situ incubations of seawater collected from an active a cold seep site at Norskebanken (north of the Svalbard archipelago) in the Arctic Ocean. For comparison, we used seawater collected from a control site (a non-seep environment). Samples were incubated with and without methane amendments. Samples amended with methane (~1 µM final concentration) showed elevated rates of MOx in both seep and non-seep incubations. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) analyses showed that the number of DOM formulas (i.e., molecular diversity) increased by up to 39